Effect of nebulized formoterol, ipratropium bromide, and furosemide in combination with fluticasone propionate on arterial blood gases of premature calves with respiratory distress syndrome - OK, M.; YILDIZ, R.; TRAŞ, B.; BAŞPINAR, N.; AKAR, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
The purpose of this study was to assess the clinical effect of nebulized formoterol (FM), ipratropium bromide (IB) and furosemide (FS) combined with fluticasone propionate (FP) on l ung function in premature calves with Respiratory Distress Syndrome (RDS). Thirty-six premature calves with RDS were randomly assigned to six different treatment groups (D1 to D6). All groups received the standard treatment, including oxygen and support treatment. Calves in D1 received only the standard treatment. The following combinations of nebulized drugs were used for the other groups: D2: FP, D3: FP+FM; D4: FP+IB; D5: FP+FS and D6: FP+IB+FM+FS. The treatment period (72 h) involved the application of FM (15 μg totally/12 h), IB (2 μg/kg/12 h), FS (1 mg/kg/12 h) and FP (15 μg/kg/12 h) for five minutes. A significant increase over time in blood pH, partial pressure of oxygen (PaO2), oxygen saturation (SatO2) and a decrease in partial pressure of carbon dioxide (PaCO2) and lactate were detected in all groups that received nebulized treatment; while in the D1, a significant change was observed only for PaCO2. Calves in D6 had the highest PaO2 and lowest PaCO2 values amongst all groups at the end of treatment. No statistical difference was observed between the Nebulization Groups (NG). Nebulized FM, IB and FS with FP combination in premature calves with RDS, in addition to the standard treatment showed a significant curative effect on lung function.